2016
DOI: 10.1080/09593985.2016.1247307
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and lasting effects of a thoracic spine manipulation in a patient with signs of cervical radiculopathy and upper extremity hyperalgesia: A case report

Abstract: Patients with cervical radiculopathy (CR) may present with accompanying symptoms of hyperalgesia, allodynia, heaviness in the arm, and non-segmental pain that do not appear to be related to a peripheral spinal nerve. These findings may suggest the presence of central or autonomic nervous system involvement, requiring a modified management approach. The purpose of this case report is to describe the treatment of a patient with signs of CR and upper extremity (UE) hyperalgesia who had a significant decrease in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
1
0
2
Order By: Relevance
“…Of this collection, 18 case studies were identified that documented improvement in total hours of sleep per night or number of sleep interruptions. The majority of case studies identified describe the benefits of correction or reduction of VS for improvement of sleep in infant and pediatric populations [ 146 , 147 , 149 , 154 , 158 , 161 , 162 , 167 , 169 - 171 , 174 ], while several case studies document similar improvements in adolescents and adults [ 151 , 153 , 155 , 156 , 159 , 173 ]. Eight trials (primarily observational, pilot, prospective, or survey-based comparative studies) outlining the quantitative benefit of spinal manipulation therapy for various aspects of sleep were identified in our search for the infant population [ 148 , 163 - 165 ], pregnant women [ 172 ], individuals with fibromyalgia (FM) [ 157 , 166 ], or in a normal asymptomatic adult population [ 150 ].…”
Section: Reviewmentioning
confidence: 99%
“…Of this collection, 18 case studies were identified that documented improvement in total hours of sleep per night or number of sleep interruptions. The majority of case studies identified describe the benefits of correction or reduction of VS for improvement of sleep in infant and pediatric populations [ 146 , 147 , 149 , 154 , 158 , 161 , 162 , 167 , 169 - 171 , 174 ], while several case studies document similar improvements in adolescents and adults [ 151 , 153 , 155 , 156 , 159 , 173 ]. Eight trials (primarily observational, pilot, prospective, or survey-based comparative studies) outlining the quantitative benefit of spinal manipulation therapy for various aspects of sleep were identified in our search for the infant population [ 148 , 163 - 165 ], pregnant women [ 172 ], individuals with fibromyalgia (FM) [ 157 , 166 ], or in a normal asymptomatic adult population [ 150 ].…”
Section: Reviewmentioning
confidence: 99%
“…Studien deuten darauf hin, dass ein multimodaler Ansatz unter Verwendung von Manueller Therapie, Übungen und Traktion zu verbesserten Ergebnissen führt und ein erfolgreiches Behandlungsergebnis vorhersagen kann [1,2,4,7,11,12]. In diesem Kontext werden unter dem Begriff "Manuelle Therapie" Mobilisations-und Manipulationstechniken an der HWS/BWS sowie neurodynamische und Weichteiltechniken verstanden [7,10,13]. "Übungen" werden als Kräftigungsübungen der tiefen Nackenflexoren und skapulothorakalen Muskulatur beschrieben [2,7] und unter "Traktion" wird sowohl eine manuelle als auch eine mechanische oder Eigentraktion per Gerät verstanden [7,14,15].…”
Section: Physiotherapeutischer Hintergrundunclassified
“…Über die Anwendung von Manipulationstechniken an der Brustwirbelsäule bei Patient*innen mit Nacken- und Armschmerzen, die im Zusammenhang mit einer zervikalen Radikulopathie (CRAD) stehen, gibt es allerdings einen Mangel an Evidenz. Deschenes et al publizierten einen Fallbericht, bei dem eine thorakale Manipulationstechnik bei der Behandlung von CRAD nützlich war, da sich die radikulären Symptome der oberen Extremität nach der thorakalen Manipulation verbessert hatten 10 .…”
Section: Zusammenfassungunclassified